SYSTEM WEB GIS POSISI OBJEK PARIWISATA DI AREA KABUPATEN ASAHAN - Yuda Prastia; Mohd Siddik; Sudarmin Sudarmin (LPPM STMIK Royal Kisaran, 2022)
Abstract: A tourist attraction is something that everyone likes, because it offers beauty and happiness for anyone who will visit it, a tourist attraction is also a source of income for each region if a tourist attraction can be developed properly of course it will increase a very high source of income, Asahan Regency is a regency located in North Sumatra. Asahan Regency has a variety of tourist attractions that can be visited, but due to lack of information and no instructions that can explain in detail where the position of the tourist attractions are located, therefore tourist attractions in Asahan Regency are less attractive to visitors. Therefore, a study was formed to overcome this problem. The problem is by making a location map to clearly determine the position of tourist objects in Asahan Regency, namely the GIS web system for the position of tourist objects in the Asahan Regency area by utilizing the Google Maps API, namely Google maps from the Google application. Keywords Geographic Information System, Tourist Objects, Position of Tourism Objects in Asahan Regency. Keywords: Tourism; Geographic Information System; Google Maps API. Abstract: Daya tarik wisata merupakan sesuatu yang disukai semua orang, karena menawarkan keindahan dan kebahagiaan bagi siapa saja yang akan mengunjunginya, suatu daya tarik wisata juga menjadi sumber pendapatan bagi setiap daerah jika suatu daya tarik wisata dapat dikembangkan dengan baik tentunya akan meningkatkan pendapatan yang sangat tinggi. Kabupaten Asahan merupakan salah satu kabupaten yang terletak di Sumatera Utara. Kabupaten Asahan memiliki berbagai tempat wisata yang dapat dikunjungi, namun karena kurangnya informasi dan tidak adanya petunjuk yang dapat menjelaskan secara detail dimana posisi tempat wisata tersebut berada, oleh karena itu tempat wisata di Kabupaten Asahan kurang diminati pengunjung. Oleh karena itu, dilakukanlah sebuah penelitian untuk mengatasi permasalahan tersebut. Yaitu adalah dengan membuat peta lokasi untuk mengetahui dengan jelas posisi objek wisata di Kabupaten Asahan yaitu sistem web GIS untuk posisi objek wisata di wilayah Kabupaten Asahan dengan memanfaatkan Google Maps API yaitu Google maps dari aplikasi Google . Kata kunci : Pariwisata , Sistem Informasi Geografis, Google Maps API.